Pengaruh Kepemilikan Institusional, Leverage Terhadap Tax Avoidance Dengan Profitabilitas Sebagai Moderating - Resiana Resiana; M. Budiantara (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to analyze the effect of Institutional Ownership, Leverage on Tax Avoidance with profitability as moderating. The population of this study is 87 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in 2020-2022.The sample of this study was determined by purposive sampling, with predetermined criteria as many as 30 companies that qualified as samples. The data used in this study were obtained from secondary data. The analysis technique used in testing data is Moderated Regression Analysis (MRA), and is processed using IBM SPSS 29 software. As a result, in Test F it was found that the variables of Institutional Ownership and Leverage did not have a significant effect on Tax Avoidance. In the T Test, Institutional Ownership and Leverage have no significant effect on Tax Avoidance. In the MRA Test it was found that Profitability did not moderate the effect of Institutional Ownership on Tax Avoidance and Profitability did not moderate the effect of Leverage on Tax Avoidance. The results showed that Institutional Ownership did not have a significant effect on Tax Avoidance, Leverage did not have a significant effect on Tax Avoidance, Profitability did not moderate the effect of Institutional Ownership on Tax Avoidance and Profitability did not moderate the effect of Leverage on Tax Avoidance.